القلق اللغوي في تعلم مهارة الكلام لدى الطالبات الجديدات بمعهد الكوثر العصري الإسلامي بانيووانجي - Al Badri, Hakiki Rikza Irnaini (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2022)
Arabic language learning as a foreign language in Indonesia has big appeal, especially the language learning. However the succeed in learning arabic at educational institutions of course it can’t be separated from problematics. One of the problem is the problem that occur at Al-Kautsar Modern Boarding School Banyuwangi. The language anxiety in learning speaking skills of Arabic happened there. This article aims to (1) Knowing the level of language anxiety in speaking skills learning, (2) Knowing the forms of language anxiety in speaking skills learning, (3) Knowing how to overcome language anxiety in speaking skills learning overcome. This research is a type of mixed method using research design (sequential mixed methods). The data collection technique used in this study is a questionnaire that refers to the HARS anxiety scale, interviews, and observations. For data analysis techniques used by researchers, namely descriptive analysis techniques for quantitative data and triangulation analysis techniques for qualitative data. After the data Analysed, can be concluded that from 25 new student, there is 52% new student who is feels anxiety at medium level and 48% other feels anxiety at low level. And from 25 new student who fill the qustionnaire, there are 12 kinds of anxiety experienced by new student while learning speaking skills of arabic. Besides that the result of qustionnaire there are two ways how to overcome the anxiety of linguistic : the external ways which is given by a teacher and internal ways comes from the new students. This External ways is related to the situational factor during learning and the Internal ways is related to psychologycal, like self perception, self conception and confidence. Keywords: Language Anxiety ; Speaking Skill ; New Students